Systematic risk and deposit insurance pricing: Based on market model and option pricing theory. Issue 4 (21st September 2017) - Zhang, Yaojie; Shi, Benshan
Abstract : Purpose: The purpose of this paper is to alleviate the moral hazard problem created by deposit insurance and therefore develop a deposit insurance pricing model explicitly considering systematic risk. Design/methodology/approach: Using the market model, the authors introduce the systematic risk component consisting of market risk and beta risk. A closed-form solution for the authors' pricing model is derived based on the option pricing framework. Findings: Compared with the authors', the pricing model that ignores systematic risk underestimates deposit insurance premium, and cannot cover the excessive loss created by systematic risk. To examine the effect of the systematic risk component on the deposit insurance premiums estimated by the authors' model, this paper also provides empirical evidence from China by regression analysis. The results demonstrate that, in addition to the individual failure risk, the systematic risk component is properly priced and explicitly reflected in the authors' model. Research limitations/implications: More risk factors such as liquidity risk should be introduced in the pricing of deposit insurance. Practical implications: Deposit insurance premiums estimated by the authors' model can alleviate the moral hazard problem that banks have an incentive to take on excessive systematic risk, because substantial higher insurance premiums would be charged in doing so. Originality/value: Applying the option pricing theory and market model, this paper develops a deposit insurance pricing model with explicit consideration of systematic risk. The systematic risk component contains not only the market volatility but also the sensitivity of market risk.